Impact of systemic diseases healing on outcomes on facial trauma patients - Bukhsh, Ayman T.; Alhouty, Monirah A.; Alosaimi, Ahmed S.; Baduwilan, Afnan M.; Alraddadi, Ibrahim S.; Fatani, Ola H.; AlSiaari, Saleh A.; Alghamdi, Yasir A.; Aljohani, Ahmed G. (International Journal Of Community Medicine And Public Health, 2025)
Facial trauma is considered a major public health issue. It is mainly caused by road traffic accidents, falls, and sports injuries. Facial trauma is associated with various functional and aesthetic adverse outcomes. The epidemiology of facial injuries differs globally, with variations in prevalence, causes, injury patterns, severity, and clinical outcomes. Facial trauma healing involves wound and fracture healing. Factors affecting healing include age, weight, and comorbidities. Systemic diseases are major determinants of the healing of injuries in various parts of the body. However, studies investigating their effects on facial trauma healing are scarce. This review aims to discuss how systemic diseases affect facial trauma healing. Diabetes induces some systemic alterations, including hyperglycemia and peripheral arterial disease, that can significantly delay healing. Chronic kidney disease delays healing through various mechanisms, including delayed granulation, disruption of keratinization kinetics, tissue edema, and large epithelial gaps. Diabetes also may impair fracture healing as a result of the elevated concentration of TNF-α at the fracture site and elevated osteoclasts in the diabetic callus. While the impact of calcium and vitamin D on fracture healing has been debatable. Although systemic diseases have a significant impact on trauma in various parts of the body, evidence on their impact on the healing outcomes of facial trauma specifically is still lacking. Thus, further research should focus on this specific topic.